PEMAHAMAN GENERASI MUDA TERHADAP PEMANFAATAN TUMBUHAN OBAT TRADISIONAL SUKU DAYAK KENYAH DESA PUNAN GONG SOLOK KECAMATAN MALINAU SELATAN HILIR - Lidia Lidia (Borneo Journal of Biology Education (BJBE), 2025)
The Dayak Kenyah tribe in Punan Gong Solok Village, South Hilir Malinau District has traditions that are still maintained to this day. One tradition that is still maintained is using plants as traditional medicine. The research goal was to determine the younger generation’s understanding regarding the use of plants as traditional medicine for the Dayak Kenyah Tribe in Punan Gong Solok Village, South Hilir Malinau District. The method used in this research was descriptive qualitative. Presentation of data through observations and interviews with 24 young generation respondents from the Dayak Kenyah tribe in Punan Gong Solok Village with an age range of 17-35 years supported by documentation. The research was conducted in October 2023. The research subjects were the young generation of the Dayak Kenyah tribe in Punan Gong Solok Village. The results showed that there were more young people from the Dayak Kenyah tribe who did not understand the use of traditional medicinal plants from the Dayak Kenyah tribe and the smallest percentage was the younger generation who understood the use of traditional medicinal plants Dayak Kenyah tribe. So, the younger the age, the less understanding the younger generation has regarding the use of traditional medicinal plants from the Dayak Kenyah tribe.